Annulment Object Gadai atas Tindakan Wanprestasi dalam Perjanjian Kredit pada Pegadaian Berdasarkan Kajian Hukum Perdata - Samuel Sihite; Vinolya Lidevia Br Manik; Pebryna Riosa Siburian; Alissa P Simbolon; Seevaira Chyta Simanullang; Parlaungan Gabriel Siahaan; Sri Hadiningrum (Departement of Mathematics Education, 2024)
Writing a report entitled Annulment of Pawn Objects for Default in Credit Agreements at Pawnshops Based on Civil Law Studies. The main purpose of writing this journal is to find out that a pawnshop is an agency or organization that operates in the field of money lending services by pawning an item as collateral. Customers who want to get loan money must pawn goods as collateral. If an agreement cannot be fulfilled or an achievement is not fulfilled, this will result in a default. What is meant by default is the non-fulfillment of achievements or obligations that have been determined towards certain parties in an agreement, whether an agreement that arises from an agreement or an agreement that arises due to law. Pawn objects are movable objects that can be tangible or intangible. such as bills, jewelry, electronic goods and motorized goods. The research method used is the empirical normative research method. The normative-empirical legal research method is a research method that includes theoretical and practical aspects in legal observation and analysis.